Nuclear Data Sheets for A=212 - Auranen, K.; McCutchan, E.A. (Nuclear data sheets, 2020)
Spectroscopic data for all nuclei with mass number A=212 have been evaluated and the corresponding level schemes from radioactive decay and reaction studies are presented. Highlights from this evaluation include the first observation of 212Hg by 2010Al24 and the first measurement of the ground state half-life by 2012Be28 and 2016Ca25. The first measurement of the β− decay of 212Tl populating excited states in 212Pb has been performed by 2014Mo02. Knowledge of excited levels and their half-lives in 212Po has been significantly extended in the transfer reaction studies of 2010As01,2010As03 and 2016Ko03,2017Ko38. A new (9−) isomer which α decays in 212At was observed by 2007Ku30. The level scheme of 212Rn was significantly extended through the (HI,xnγ) reaction studies of 2009Dr12 and 2008Dr01. New levels in 212Ra were identified in a transfer reaction experiment by 2018Pa04. Finally, the α decay of both the ground state and an isomer in 216U populating 212Th was reported for the first time by 2015Ma37 and 2015De22.